A pregação e a comunidade : reflexões morais e sobre a origem da sociedade humana nos sermões de Giordano de Pisa, O.P. (1302-1309) - Aléssio Alonso Alves (2018)
This thesis deals with the theme of morality and the origin and configuration of human society as found in the reportationes (i.e. transcriptions) of Giordano da Pisa’s preaching in Florence and in his hometown in the first decade of the fourteenth century. The study addresses two recurring themes among the men of knowledge of the thirteenth and fourteenth centuries; however, the second one, that of the human society, has so far been little investigated by historiography through the use of sermonary sources. The analysis of both these themes are important not only for the understanding of the development of this debate in the space-time frame dealt with, but precisely for showing how a Dominican Preacher of intense performance in two of the most important communes of the Italic Peninsula of the beginning of the fourteenth century developed and exposed these themes to a lay public in the act of preaching; and how he tried to shape the customs and direct the actions of his audience based on these considerations. Therefore, the documentary corpus of this work is composed by some of the 731 reportationes of the preaching of Giordano held both in Florence and in Pisa. The goals of this work are achieved, firstly, by analyzing and comparing sermons of the same thema. By doing so, the arguments used by Giordano concerning the themes of this study are emphasized and it is sought to examine them in reference to the authorities employed by the friar and the manner in which he appropriated these ideas to propose moral reflections and certain considerations about the origin and configuration of human society, as well as to model customs and guide the actions of listeners. Thereby, the comparison of the sermons demonstrates the approximations and distances between the sermons of the same thema, pointing out the possible explanations for the differences. By means of these analyses, it is first demonstrated that Giordano, in regard to moral debate, remained very close to a political discussion on vices and virtues as undertaken by the men of knowledge of his time. Secondly, as regards the subject of the origin of human society, it is proved that the preacher oscillated between a naturalistic conception of Aristotelian basis and a Augustinian voluntarist one according to the requirements of the liturgical context, that is, the thema of the sermon and the subjects it proposed and which were commonly dealt with at that liturgical date. As a result, the preacher did not establish a single judgment on the positivity or negativity of human politics and society, adapting his appreciation to the liturgical context. Although this makes it impossible to speak of a finished giordanian sociopolitical theory, the importance of studying this subject from these documentary sources is justified by the fact that preaching was one of the moments in which the lay public established contact with the discussions and political debates developed in circles of academic and conventual knowledge.